Numerical investigation of moisture movement in wood under isothermal conditions - Baronas, R.; Ivanauskas, F.; Sapagovas, M. (Mathematical Modelling and Analysis, 2001)
The present work summarizes the results of several previous studies on moisture movement in wood during drying under isothermal conditions. A model of the wood drying taking into consideration coating of the surface of a specimen is presented in three‐dimensional‐in‐space (3‐D) formulation. The influence of the geometrical shape as well as surface coating degree of wood specimens from the northern red oak (Quercus rubra) on the drying dynamics is investigated. The conditions of usage of 2‐D moisture transfer model in contrast to 1‐D for accurate predicting of the drying process are described.Drėgmės judėjimo medienoje izoterminėmis sąlygomis modeliavimasSantrauka. Šiame darbe yra apžvelgiama keletas ankstesnių darbų, kuriuose buvo nagrinėjama drėgmės judėjimas medienoje džiovinant ją izoterminėmis sąlygomis. Straipsnyje yra pateiktas trimatis medienos džiovinimo modelis, kuriame atsižvelgiama į galimą bandinio paviršiaus izoliavimą. Bandinio geometrinės formos bei paviršiaus izoliavimo lygmens įtaka džiūvimo dinamikai yra ištirta bandiniams, pagamintiems iš šiaurės ąžuolo (Quercus rubra). Darbe yra išanalizuotos sąlygos, nusakančios, kuomet yra tikslingiau naudoti dvimatį modelį vietoje atitinkamo vienmačio modelio.First Published Online: 14 Oct 2010